The Effects of Double-Blind versus Single-Blind Reviewing: Experimental Evidence from The American Economic Review - Blank, Rebecca M. (American Economic Review, 1991)
The results from a randomized experiment conducted at The American Economic Review on the effects of double-blind versus single-blind peer reviewing on acceptance rates and referee ratings indicate that acceptance rates are lower and referees are more critical when the reviewer is unaware of the author's identity. These patterns are not significantly different between female and male authors. Authors at top-ranked universities and at colleges and low-ranked universities are largely unaffected by the different reviewing practices, but authors at near-top-ranked universities and at nonacademic institutions have lower acceptance rates under double-blind reviewing.